2017
DOI: 10.1186/s12870-016-0952-8
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of PaNAC03, a stress induced NAC gene family transcription factor in Norway spruce leads to reduced flavonol biosynthesis and aberrant embryo development

Abstract: BackgroundThe NAC family of transcription factors is one of the largest gene families of transcription factors in plants and the conifer NAC gene family is at least as large, or possibly larger, as in Arabidopsis. These transcription factors control both developmental and stress induced processes in plants. Yet, conifer NACs controlling stress induced processes has received relatively little attention. This study investigates NAC family transcription factors involved in the responses to the pathogen Heterobasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 83 publications
(125 reference statements)
0
38
0
Order By: Relevance
“…Flavonoids accumulation in Norway spruce (Picea abies) increased the resistance against the fungal pathogen Heterobasidion annosum [129]). Recently, it was revealed that PaNAC03 responded against infection of H. annosum by negatively regulating some flavonoid biosynthetic genes, such as CHS, F3'H, and LAR3 [107]. Moreover, ANACO32 has also been identified as a negative regulator of anthocyanin biosynthesis.…”
Section: Nac Tfsmentioning
confidence: 99%
“…Flavonoids accumulation in Norway spruce (Picea abies) increased the resistance against the fungal pathogen Heterobasidion annosum [129]). Recently, it was revealed that PaNAC03 responded against infection of H. annosum by negatively regulating some flavonoid biosynthetic genes, such as CHS, F3'H, and LAR3 [107]. Moreover, ANACO32 has also been identified as a negative regulator of anthocyanin biosynthesis.…”
Section: Nac Tfsmentioning
confidence: 99%
“…Other transcription factors, apart from R2R3-MYBs and bHLHs, e.g., Basic Leucine Zipper Domain (bZIP) or NAC, have been reported as positive regulators of flavonoid biosynthesis (Morishita et al 2009;Malacarne et al 2016). The single repeat MYBs (R3-MYBs), squamosa promoter binding protein like (SPL), or some NAC TFs, have been reported as negative regulators of flavonoid biosynthesis in plants (Dubos et al 2008;Gou et al 2011;Dalman et al 2017). The R3-MYB and SPL are known to repress flavonoid biosynthesis by disrupting the formation of the MYBbHLH-WD40 complexes.…”
Section: Regulation Of Flavonoid Biosynthesis In Plants: a Comparisonmentioning
confidence: 99%
“…Previously, MYB, bHLH and WD40 proteins have been found to regulate flavonoid biosynthesis by governing the expression of flavonoid synthesis genes (Lotkowska et al ., ). In addition, NAC‐type, WRKY‐type, MADS‐type and bZIP‐type transcriptional factors have also been identified as regulators of the flavonoid biosynthesis pathway (Jaakola et al ., ; Amato et al ., ; Dalman et al ., ; Lloyd et al ., ). Here, we found that soybean NAC‐type transcription factor GmNAC2 is a direct negative modulator of flavonoid biosynthesis.…”
Section: Discussionmentioning
confidence: 98%